Presence of blood parasites in the yellow-footed tortoise (Chelonoides denticulata) (Linnaeus, 1766) sold at the Belen market, Iquitos, Peru - Batalla L., Luis (2015)
The aim of this study was to identify and determine the presence of blood parasites in yellow-footed tortoises sold in the market of Belen, Iquitos, Peru and their association with sex, body weight, hematocrit and parasitemia. Blood samples were collected from 47 tortoises in July 2010. The thin blood smears with Giemsa, the microcapillary Woo technique and the Buffy coat technique were used for the identification of the haemoparasites. The results showed the presence of Haemogregarina sp in 74.5% of the samples, being 68.8% in females and 86.7% in males. There were mature gamonts (11.09 ± 1.42 μm length x 5.82 ± 0.76 μm wide) and inmature gamonts (14.85 ± 0.69 μm x 3.26 ± 0.41 μm). There were no significant differences between the presence of the parasite and the variables sex, weight, hematocrit and parasitemia level.